Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1103/physrevlett.108.103002
|View full text |Cite
|
Sign up to set email alerts
|

Laser Radiation Pressure Slowing of a Molecular Beam

Abstract: We demonstrate deceleration of a beam of neutral strontium monofluoride molecules using radiative forces. Under certain conditions, the deceleration results in a substantial flux of detected molecules with velocities ≲50  m/s. Simulations and other data indicate that the detection of molecules below this velocity is greatly diminished by transverse divergence from the beam. The observed slowing, from ∼140  m/s, corresponds to scattering ≳10(4) photons. We also observe longitudinal velocity compression under di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
178
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(184 citation statements)
references
References 56 publications
2
178
0
3
Order By: Relevance
“…They first demonstrated the technique for SrF. [63][64][65] More recently, Hummon et al 66 have applied the scheme to cool YO while Zhelyazkova et al 67 have demonstrated it for the CaF molecule.…”
Section: A Methods For Creation Of Cold and Ultracold Moleculesmentioning
confidence: 99%
“…They first demonstrated the technique for SrF. [63][64][65] More recently, Hummon et al 66 have applied the scheme to cool YO while Zhelyazkova et al 67 have demonstrated it for the CaF molecule.…”
Section: A Methods For Creation Of Cold and Ultracold Moleculesmentioning
confidence: 99%
“…week ending 29 SEPTEMBER 2017 133002-3 vibrational repumpers, enabling longitudinal slowing [35] and direct magneto-optical trapping [7].…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
“…Molecules in the low velocity tail of such a buffer gas beam can be selected (26,27), trapped (28,29) and cooled (30). Recently, buffer-gascooled beams of a few molecular species have been slowed to low velocity using radiation pressure (31)(32)(33)(34)(35), and CONTACT S. Truppe s.truppe09@imperial.ac.uk The underlying research materials for this article can be accessed at Zenodo (https://doi.org/10.5281/zenodo.995663) and may be used under the Creative Commons CCZero license. these slow molecules have been captured and cooled to low temperatures in magneto-optical traps (36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%